Effect of capacitive radiofrequency on the dermis of the abdominal region - Laguna Monaretti, Gabriela (2021)
The purpose of this study is to evaluate the effects of radiofrequency (RF) on sagging skin. This is a case series study with five volunteers who received a single application of capacitive RF (BTL-6000 TR-Therapy Pro®) in the right infraumbilical abdominal region, with epidermal temperature above 40°C, for 10 min (2 min per applicator area), and the skin of the contralateral region was used as control. After 30 days, on average, the skin of the abdominal region was collected for histological analysis and stained with hematoxylin and eosin, Picro-sirus, and Verhoff. The percentage of collagen and elastic fibers found was marked by the Image J®. The statistical analysis was performed in the SPSS program (version 20), with a significance level of 95%. This was registered with the ethics and research comitee of UFTM n 3.461.688 on Jul 12, 2019 and clinical trial registration n. NCT04182542, retrospectively registered. Morphometric analysis demonstrated a remodeling of collagen and elastic fibers on the side treated with RF; however, the morphometry for collagen showed no significant difference, with an average percentage of 60.94 ± 0.32 for the control side and 61.97 ± 2.80 for the treated with p=0.32. Similarly, elastic fibers also showed no significant difference between groups, with a mean percentage of 5.67 ± 2.70 for control and 6.21 ± 2.01 for treated with p=0.19. The RF with the parameters used in this study was able to cause morphological changes in collagen and elastic fibers of the abdominal region skin; however, it showed no change in the percentage of these fibers.